Novas formas de financiamento de intervenções de conservação e restauro : mecenato, patrocínio e crowdfunding - Sousa, Ana Isabel de Sousa Martins Guerin de, 1977- (2018)
The present dissertation aims to study patronage, sponsorship and crowdfunding models as means for alternative financing of conservation and restoration interventions of national mobile and integrated cultural assets, which would traditionally be supported by the State and its institutions. The research begins by defining what is cultural assets, based on the base Law of Cultural Heritage (Law no. 107/2001, of September 8), and its legal provisions in order to contextualize them in this study. Given the scarcity of information on the conservation status of these cultural assets, a questionnaire was prepared, entitled "The role of conservation and restoration in Portuguese museums", in order to understand the necessities of national collections. This survey corroborated the deficiencies of conservation and restoration in museological collections, as well as the lack of human resources specialized in this field. The Portuguese population in the use of these financing models was also verified, in order to understand their viability and possible utility in solving the problem. Once again resorting to public inquiry, a new questionnaire of multiple responses was executed, entitled "New forms of financing for interventions for the conservation and restoration of cultural assets". After analyzing all the data collected, both from the point of view of museum deficiencies and public participation, the creation an exclusive platform to finance conservation and restoration interventions of mobile and integrated cultural assets in Portuguese territory, was proposed. The aim is to overcome the lack of investment in the area, which has contributed to the constant deterioration of cultural assets. This project, which we call the Heritage Support Platform (HSP), presents two distinct phases of implementation: the first is through crowdfunding, which has more media coverage, and the second, through the implementation of sponsorship and patronage projects that create a link between people / companies and institutions which hold cultural assets. HSP intends to be the first Portuguese crowdfunding channel which is exclusively dedicated to supporting conservation and restoration projects of mobile and integrated heritage, which simultaneously appeals to the Portuguese population's awareness of the need to preserve and protect their heritage